KEPADATAN POPULASI DAN SEBARAN CACING TANAH DI LAHAN SAWAH SISTEM PERTANIAN ORGANIK, SEMI ORGANIK DAN KONVENSINAL - Anwar, Ea Kosman; Simanungkalit, RDM.; Santoso, Edi; Sukristiyonubowo, Sukristiyonubowo (Universitas Atma Jaya Yogyakarta, 2010)
Earthworm is one of the soil macrofauna, which consumes organic matter for body growth and life. Therefore the earthworm can be soil organic status and soil fertility indicator. On the other hand, at present, the organic farming system is developing and positively accepted by people as yield consumer, and yield price is higher than conventional yield price. The experimen to study the earthworm population rate and spread methode was conducted in 2008 planting season, in West Java, with RBD (Randomized Block Design). Three farming system as treatment i.e Organic farming, Semi organic and Conventional farming system and six location as replication. The result showed that Semi organic farming system is the most earthworm population rate and the earthworm distribution is random model.